Formulation of Fibrauren tinctoria Lour. Extract Serum, As an Antioxidant with the 1,1-Diphenyl 2-Picryhydrazyl (DPPH) Method - Wijayanto, Arif; Herdianty, Juvita; Putri, Luluk Aniqoh Meliana; Sumanto, Ardhi Broto (Open Access Health Scientific Journal, 2025)
Background: Serum is a preparation with a high concentration of active ingredients and low viscosity, which delivers a thin film of active ingredients to the skin surface. The use of Fibraurea tinctoria has been carried out since ancient times by the Dayak, Banjar, and Kutai tribes as a traditional treatment for liver disease, diabetes, and to increase the body's immunity from various causes of disease such as bacteria. Fibraurea tinctoria is believed to be able to ward off the negative effects caused by free radicals such as antioxidants.Methods: This experimental study investigated the antioxidant activity of Fibraurea tinctoria extract serum with varying concentrations of hydroxyethyl cellulose 1.0%, 1.5%, and 2.0% using the DPPH methods, which is simple, easy, fast, and sensitive, and requires a small sample. This method provides information on the reactivity of the tested compound with a stable radical. Evaluations of the Fibraurea tinctoria extract serum preparation was carried out by observing the results of physical quality tests, including organoleptic tests, homogeneity tests, pH tests, adhesion tests, and spreadability tests. The serum preparation was tested for 3 days and stored at room temperature. Data were analyzed descriptively by comparing it with the Indonesian National Standard.Results: The results showed that the serum extract preparations of Fibraurea tinctoria F1st, F2nd, and F3rd showed varying IC₅₀ values, where lower values ​​indicated stronger antioxidant potential. Formulation F3rd showed the lowest IC₅₀ value (3.11 ppm), F2nd (3.74 ppm) and F1st (4.67 ppm), all of which were stronger than the base (5.11 ppm).Conclusion: In this research, formulations F1st, F2nd, and F3rd had the highest antioxidant activity, with F3rd at a concentration of 2.0%. The identified strong antioxidant activity is the main basis for the potential of Fibraurea tinctoria extract serum as an active antioxidant ingredient.